The Comparison of Impact of Myo-inositol in combination with Metformin versus Metformin alone on Androgenic Features of PCOS patients - Khattak, Hira Ehsan; Mahrukh, Syeda Khadija; Ullah, Atif; Zahid, Muhammad; Gul, Sadia; Khan, Ayesha (Journal of Rawalpindi Medical College, 2026)
Objective: To compare the effects of a combination of Myo-inositol and Metformin versus Metformin alone on hirsutism and acne in PCOS patients. Methods: A total of 114 adult PCOS patients with hirsutism as well as acne underwent an 8-months randomization (September 2022 to May 2023) at Khyber Teaching hospital Peshawar outpatient department of gynecology and obstetrics, to one of the two treatments (double blinded study), where Group A included of 57 individuals taking combination of 500 mg of oral Metformin three times each day and Myo-inositol 4000 mg once daily; Group B included 57 individuals taking 500 mg of oral Metformin three times each day as single therapy. All hormonal, metabolic, and clinical indicators were assessed at the initial and eight-month points after the commencement of medication. Results: A Significant difference was noted in terms of mean change in Farriman-Gallwey score in Group A (n=55), 3.59±0.81, versus Group B (n=54), 4.68±0.55 (p=0.00). Similarly, there was a notable improvement in mean change in Global acne score in Group A 1.51±0.50 when compared to Group B 2.38±0.67 (p =0.00), similarly there was significant differences between Group A 33.2±3.01 and Group B 41.5±32.99 in terms of mean serum Total testosterone levels p=0.00 and significant difference between Group A 95.56±5.71 and Group B 146.70±15.75 in terms of mean serum DHEA levels p=0.00. Conclusion: By balancing hormones and improving metabolic profile, Myo-inositol and Metformin, when used in combination, are more successful in treating hirsutism and acne in adult PCOS patients as compared to metformin alone. Keywords: Polycystic ovarian syndrome, hirsutism, myo-inositol, metformin